Response of Some Productive and Qualitative Characteristics of the Local Tobacco Variety (Nicotiana tabacum L.) Under the Influence of Phosphorus Treatment and Sorbitol Foliar Spraying (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
A factorial experiment with a randomized complete block design (RCBD) and three replications was conducted in 2025 in an agricultural area in the village of Al-Salata, Qardaha District, Latakia Governorate, and in the research laboratory of the Field Crops Department, Faculty of Agricultural Engineering, Latakia University. The local variety, Shek Al-Bint, was used, with seeds obtained from the General Tobacco Corporation, Latakia. To test the effect of foliar application of sorbitol (S) at the following concentrations (0, 1, 1.5, 2 g/L) and phosphorus (P) fertilization (0, 30, 60, 90 kg/ha) on some growth indicators, productive, qualitative, and technological characteristics of local tobacco, and to determine the optimal fertilization and application concentrations.Foliar application of 2 g/L sorbitol and phosphorus fertilization at a rate of 90 kg/ha, both individually and in combination, resulted in a significant increase in most of the studied characteristics, especially in the S3P3 treatment (90 kg/ha with 2 g/L). This increase was observed in the following characteristics: plant height (cm), leaf surface area (cm²), photosynthetic efficiency (g/cm²/day), leaf thickness (µm), green and dry leaf yield (kg/dunum), and sugar content (%). Additionally, the nicotine content (%) was reduced. Therefore, we recommend treating the local tobacco (Shak al-Bint) in the study area with both sorbitol spray at a concentration of 2 g/L and phosphorus fertilization at a rate of 90 kg/ha, either individually or together at the same concentrations, due to their stimulating physiological role in improving most plant growth indicators compared to the control.
Keywords: Local tobacco (Shak al-Bint), sorbitol, phosphorus fertilizer.